ANALISIS AERODINAMIKA UNTUK DESAIN MOBIL LISTRIK JENIS KARGO MINI - Azis Amir Allah; Tri Mulyanto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
As an effort to expand the development of electric vehicles, one of the steps is to design an aerodynamic body for electric cars. An aerodynamic body design can reduce drag forces acting on the vehicle, thereby saving energy usage. A key aspect to consider in aerodynamic design is the drag coefficient (Cd) value; the smaller the Cd value, the greater the energy efficiency and overall vehicle performance. Therefore, this study aims to design an aerodynamic body for a mini cargo electric car, which can later serve as a reference design for mini cargo electric vehicles. The simulation was conducted using ansys fluent 2023 R1 software with the computational fluid dynamics (CFD) method. Initial validation was performed using the Ahmed body design. Simulations were carried out with speed variations of 20 km/h, 30 km/h, 40 km/h, 50 km/h, and 60 km/h. The results of the study showed that the lowest Cd value occurred at a speed of 60 km/h, with a Cd value of 0,458. Thus, at a speed of 60 km/h, the mini cargo electric car will have better energy efficiency and vehicle performance compared to other speeds.